2021
DOI: 10.1038/s41467-020-20249-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-domain translation between single-cell imaging and sequencing data using autoencoders

Abstract: The development of single-cell methods for capturing different data modalities including imaging and sequencing has revolutionized our ability to identify heterogeneous cell states. Different data modalities provide different perspectives on a population of cells, and their integration is critical for studying cellular heterogeneity and its function. While various methods have been proposed to integrate different sequencing data modalities, coupling imaging and sequencing has been an open challenge. We here pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 30 publications
0
91
0
Order By: Relevance
“…By training these VAE variants on L1000 gene expression readouts resulting from the same set of compound perturbations, we observed large differences in optimal hyperparameters as compared to training on Cell Painting image-based data (Subramanian et al, 2017;Xue et al, 2020). These observations indicate that the KL divergence penalty strongly influences cell morphology modeling ability, and that lessons learned by modeling other biomedical data types, such as gene expression, will not necessarily directly translate to cell morphology (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…By training these VAE variants on L1000 gene expression readouts resulting from the same set of compound perturbations, we observed large differences in optimal hyperparameters as compared to training on Cell Painting image-based data (Subramanian et al, 2017;Xue et al, 2020). These observations indicate that the KL divergence penalty strongly influences cell morphology modeling ability, and that lessons learned by modeling other biomedical data types, such as gene expression, will not necessarily directly translate to cell morphology (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Apart from the feature-converted data, Seurat v3 15 and bindSC 30 also devised heuristic strategies to utilize information in the original feature space, which probably explains their improved performance than methods that do not 16, 17 . At the cell level, known cell types have also been used via (semi-)supervised learning 47, 48 , but this approach incurs substantial limitations in terms of applicability since such supervision is typically unavailable and in many cases serves as the purpose of multi-omics integration per se 26 . Notably, one of these methods was proposed with a similar autoencoder architecture and adversarial alignment 48 , but it relied on matched cell types or clusters to orient the alignment.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, modality alignment becomes paramount ( Lopez et al, 2019 ). A recent work integrating single-cell RNA-sequencing data and single-cell nuclear-imaging of naive T-cells ( Yang et al, 2021 ) has shown that DL representation of images contain signals predictive of true fold change of gene expression between different classes of cells.…”
Section: Going Further With Deep Learningmentioning
confidence: 99%